Mortal Fear - Cook, Robin (New York Berkley Books, 1989)
Robin Cook is back--with his most provocative bestseller. A harrowing medical nightmare that goes beyond the shocking chills of Coma and the sweeping panic of Outbreak ... into the controversial future of genetics. "A chilling odyssey into the origins of life--and death".--USA Today.
Keywords: Horror tales -- Genetics--Research -- Physicians